Patients in Permanent Vegetative State – Biomedical and Constitutional Questions - Rajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The issue of termination of life of patients in a permanent vegetative state redefines a traditional concepts and understanding of basic categories of human life, bringing the constitutional values into direct conflict. There is no clear position on the issue of stopping the procedure of artificial nutrition and hydration of patient in persistent vegetative state. Legal systems show differences in access of solving these problems, although, in principle, accept the possibility of denial of such a medical procedure. Discussion is still opened about does that kind of life maintain the minimum requirements of dignity and respect of personal integrity or not and is it more human let such life to be ended.
Keywords: the case of Eluana Englaro; collision of constitutional values; termination of medical care; irreversible loss of consciousness; permanent vegetative state; Biomedicine